Children 'under lockdown': voices, experiences, and resources during and after the COVID-19 emergency. Insights from a survey with children and families in the Lombardy region of Italy. Issue 1 (2nd January 2021) - Mantovani, S.; Bove, C.; Ferri, P.; Manzoni, P.; Cesa Bianchi, A.; Picca, M.
ABSTRACT: The article presents preliminary findings from a family survey about children's experiences during the COVID-19 lockdown, which was administered through the pediatric network SICuPP (Italian Society of Primary Care Pediatricians – Lombardy) in Northern Italy. The study involved 3443 parents with children aged from 1 to 5 years and from 6 to 10 years living in Lombardy region, the earliest and most severely affected by the COVID-19 emergency. All participants completed an online questionnaire and provided informed consent. Respondents generally displayed confidence and a sense of self-efficacy in relation to how they had coped with the COVID-19 emergency, despite the many difficulties encountered during the lockdown. They reported having observed some unexpected improvements and resources (e.g. parent/child and sibling relationships, adaptiveness and autonomy on the part of children). Parent-to-parent solidarity was commonly reported, although a small percentage of parents had experienced a greater sense of isolation and anxiety. Finally, the study indicated 'key areas of vulnerability' (concerning, for example, eating, rules, sleeping, use of technological devices, fears …) that should be monitored in future by strengthening the territorial network linking families, educational services, and health services.